Synthesis of N-phenethyl-p-methoxycinnamamide and N-morpholinyl-p-methoxycinnamamide, In Vitro and In Silico Study as α-Glucosidase Inhibitor - Herlina Rasyid; Firdaus Firdaus; Syadza Firdausiah; Nunuk Hariani Soekamto; Seniwati Seniwati; Riska Mardiyanti; Reynaldi Reynaldi; Andi Eka Sri Rahayu; Wahyu Dita Saputri (Universitas Gadjah Mada, 2022)
Aromatic ginger (Kaempferia galanga L.) is one of the natural sources containing ethyl-p-methoxycinnamate, which is known to have beneficial activity, especially as an α-glucosidase inhibitor. This study aims to convert ethyl-p-methoxycinnamate into amide form as N-phenethyl-p-methoxycinnamamide (4a) and N-morpholinyl-p-methoxycinnamamide (4b) through some synthetic ways then tested their activity as an α-glucosidase inhibitor. The FTIR spectra of 4a present a short single peak at 3269.34 cm−1 that belongs to the N-H group, while spectra of 4b show no absorption band between 3200–3400 cm−1 due to its tertiary amide structure. Spectroscopy analysis through 1H- and 13C-NMR exhibits the successful synthesis of both compounds. Bioactivity test results show that compound 4b has better activity than 4a. In molecular dynamics simulation, the binding energy of compounds 4a and 4b reveal that both compounds have a similar binding energy of about -98980.8 and -97696.7 kJ mol−1, respectively.